MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS IX F SMPN 1 SUNGGUMINASA - Muh. As'af Alhidayat. R; Suci Pratiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve the learning outcomes of class IX F students at SMPN 1 Sungguminasa in the Pancasila Education subject by using the Student Facilitator and Explaining learning model. This research was conducted at SMPN 1 Sungguminasa with the subject Pancasila Education. The subjects in this research were class IX F students with a total of 33 students consisting of 18 female students and 15 male students. The timing of the research refers to the school's academic calendar or to be precise, it will be carried out in the even semester of the 2024 academic year. The type used in this research is Classroom Action Research (PTK). Based on the results of the analysis from this research, it can be seen that with the Student Facilitator and Explaining learning model, student learning outcomes have increased from cycle 1 to cycle II. In cycle I, student learning outcomes reached 81.81% completeness, in cycle II they achieved 90.90% completeness. Based on the results of the analysis, it can be concluded that using the Student Facilitator and Explaining learning model can improve student learning outcomes in the Pancasila Education subject.